Pemanfaatan Pembangunan Sistem Pengelolaan Air Minum (SPAM) Regional Mebidang pada Masyarakat di Jalan Medan-Binjai - Simamora, Irma Yusriani; Tanjung, Saydina Maya; Fahira, Jirza Raisa; Walid, Muhammad; Syahputra, Diky (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Development of a Drinking Water Management System (SPAM) is an important effort to meet the community's need for clean water. This study aims to determine the utilization of SPAM development for people who live on Jalan Medan-Binjai. The method used in this research is data collection through surveys, interviews, and field observations. The data obtained were analyzed using a qualitative approach. The results of the study show that the construction of a SPAM on Jalan Medan-Binjai provides significant benefits for the community. However, this study also identified several challenges in the utilization of SPAM on Jalan Medan-Binjai. These challenges include the lack of public awareness in maintaining cleanliness and efficient use of water, as well as coordination between the government and the community in optimizing SPAM utilization. Keywords: Clean Water, Community, Medan City